The thermodynamics of indoor air pollution: A pilot study emulating traditional Kenyan homesteads. (February 2020) - Haggerty, Lauren; Reischl, Uwe; Handy, Rodney G.; Sleeth, Darrah K.; Adams, Karin; Schaefer, Camie
Highlights: Hot air flows to cooler air, thus smoke and air pollution is dispersed more quickly in environments with greater temperature differentials. The addition of windows to a simulated Kenyan homestead would decrease temperature differentials within the enclosed kitchen hut. Effective interventions for Kenyan homestead require more than the simple addition of windows. Follow-on research from this project was used to develop an alternative homestead design placing the stove in an exterior, yet accessible location. Abstract: This study examined the addition of natural ventilation (i.e., windows) in traditional Kenyan homesteads and other similar dwellings in developing countries. There is a particular need for the reduction of indoor air pollution in Kenya and other countries where traditional cooking relies on unrefined biomass fuels. For the purposes of this study, a cardboard tower equipped with thermocouples and an 80-watt heat source was constructed. As the recreation of smoke was deemed unfeasible, temperature differentials were measured within the tower and examined how varying temperature conditions might contribute to the accumulation of smoke indoors. Two scenarios were tested: windows-open and windows-closed. In the windows-open scenario, decreased temperature differentials were consistently observed throughout the sampling process with an average of 4.8 °C less than with the windows-closed (p = <0.0001). As existing research on smoke movement and temperature demonstrates, a decreased temperature differential will contribute to smoke stratification and an increased exposure to indoor air pollution. This study suggests that additional natural ventilation in isolation does not necessarily improve indoor air quality among households that use traditional cooking practices similar to Kenya's. Rather, alternative interventions should be designed, including the placement of an exterior stove that is shielded from the elements but accessible to those indoors.